The Effect of Motivation, Competency and Commitment on Employee Performance: The Case of Ogan Ilir Regency’s Regional Secretariat - Yuliani, Yuliani; Idris, Muhammad; Choiriyah, choiriyah (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
This study determines Work Motivation, Competence, and Organizational Commitment to the Performance of Ogan Ilir Regency Regional Secretariat Employees. The object of this study is an employee of the Regional Secretariat of Ogan Ilir Regency. The method used is quantitative research with a data collection model and questionnaires. The population in this study was 153 employees in the Regional Secretariat of Ogan Ilir Regency; the determination of the number of samples in this study using the determination of samples from the population by Isaac and Michael (error rate 5%), So that the sample amounted to 105 respondents. The analysis technique used is multiple linear regression. The results of this study show that 1) simultaneously, Work Motivation, Competence, and Organizational Commitment have a significant effect on the Performance of Ogan Ilir Regency Regional Secretariat Employees. 2) Work Motivation significantly affects the Performance of Ogan Ilir Regency Regional Secretariat Employees. 3) Competence significantly affects the performance of employees of the Regional Secretariat of Ogan Ilir Regency. 4) Organizational commitment does not significantly affect the performance of employees of the Regional Secretariat of Ogan Ilir Regency